Hukum Kekerasan Anak dalam Perspektif Filsafat Hukum: Analisis atas Keadilan dan Hak Asasi Manusia di Indonesia - Agus Panahatan Panjaitan; Adi Putra Prajitna; Ade Nugroho; Agung Ramanto (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The Child Protection Law affirms that the state guarantees children's rights to “protection from violence” as stipulated in the 1945 Constitution. This paper examines child abuse within the framework of Indonesian positive law using a normative approach and legal philosophy (positivism). The focus of the analysis is to what extent legal norms (such as the Child Protection Law, the Criminal Code, the Domestic Violence Law, etc.) align with the values of justice and children's human rights. A normative approach is used to analyze the laws and legal literature, while the philosophical approach, particularly the positivist ideas of Hans Kelsen and H.L.A. Hart, is employed to understand the relationship between legal norms and the concept of justice. The analysis reveals that although child protection regulations exist, their implementation on the ground tends to be legalistic, often neglecting humanitarian and justice elements. This study emphasizes the need for alignment between legal norms and substantive justice and the protection of children's human rights. The implication of this research is the need for a legal policy that is more responsive to children's rights and justice.